Answer:
Vertex form
y = -4(x + 3)^2 + 10
Standard form;
y = -4x^2-24x - 26
Step-by-step explanation:
Mathematically, we have the vertex form as
y = a(x-h)^2 + k
(h,k) represents the vertex
We have h as -3 and k as 10
y = a(x+3)^2 + 10
To get a, we substitute any of the points
Let us use (-1,-6)
-6 = a(-1+3)^2 + 10
-6-10 = 4a
4a = -16
a = -16/4
a = -4
So we have the equation as;
y = -4(x+3)^2 + 10
For the standard form;
We expand the vertex form;
y = -4(x + 3)(x + 3) + 10
y = -4(x^2 + 6x + 9) + 10
y = -4x^2 - 24x -36 + 10
y = -4x^2 -24x -26
Answer:
13 cups
Step-by-step explanation:
If the small box has 10 cups, then:
<u> (small) </u> <u> 10 cups </u> = <u> 100% </u>
(medium) x cups = 130%
Now, cross multiply:
10 (130) = x (100)
1300 = 100x
x = 13
Another way to solve this is by turning 30% into a decimal:
30/100 = 0.3
10 (0.3) = 3
Now you have 30% of the 10 cups, but you need <u>30% more</u><em> </em>than the small box, so:
10 + 3 = 13 cups
Operations that can be applied to a matrix in the process of Gauss Jordan elimination are :
replacing the row with twice that row
replacing a row with the sum of that row and another row
swapping rows
Step-by-step explanation:
Gauss-Jordan Elimination is a matrix based way used to solve linear equations or to find inverse of a matrix.
The elimentary row(or column) operations that can be used are:
1. Swap any two rows(or colums)
2. Add or subtract scalar multiple of one row(column) to another row(column)
as is done in replacing a row with sum of that row and another row.
3. Multiply any row (or column) entirely by a non zero scalar as is done in replacing the row with twice the row, here scalar used = 2
Answer:
Sigh no body wants to answer this one, so I'll just take my points back
The answer is D) 602.88
Example: The formula is V= pi r*r*h V = 3.14 (4* 4) (12) V = 3.14 (16) (12)
V= 3.14 * 192 = 602.88m squared